Sodium polystyrene sulfonate as an additional contributing factor to repeated gastric ulcers among other multiple factors in a patient undergoing hemodialysis: a case report - Yukiko Yasui; Akio Nakashima; Kosuke Sasuga; Kentaro Koike; Izumi Yamamoto; Yoshimi Ueda; Goro Tokudome; Ichiro Ohkido; Takashi Yokoo (BMC Nephrology)
Abstract Background Sodium polystyrene sulfonate (SPS) is a cation-exchange resin used to treat hyperkalemia. Although colorectal ulcers are known side effects of long-term SPS use, few studies have reported SPS-associated gastric ulcers. Herein, we report a case of repeated gastric ulcers during SPS administration. Case presentation The patient was a 55-year-old man who was on SPS treatment of hyperkalemia since the initiation of hemodialysis (HD) at the age of 51 years. At the age of 54 years, he started taking vonoprazan fumarate after developing a bleeding duodenal ulcer. The patient underwent laparoscopic pylorus-preserving gastrectomy for four recurrent bleeding gastric ulcers. The resected specimen showed an ulcerative lesion in the pyloric curvature of the stomach, and pathological findings showed deposition of a basophilic crystalline substance resembling a cation-exchange resin at the base of the ulcer. Conclusion In this case, various factors, including diabetic gastroenteropathy, use of multiple calcium channel blockers and phosphate binders, obesity, and lifestyle, contributed to decreased gastrointestinal peristalsis. This may have promoted SPS deposition in the stomach, potentially leading to ulceration.